2006
DOI: 10.1021/pr060010k
|View full text |Cite
|
Sign up to set email alerts
|

Profiling of Glycans in Serum for the Discovery of Potential Biomarkers for Ovarian Cancer

Abstract: A glycomic approach is developed to identify oligosaccharide markers for ovarian cancer by rapidly profiling globally released oligosaccharides. Glycoproteins shed by cancer cells are found in the supernatant (or conditioned media) of cultured cells. In this approach, shed glycoproteins are profiled for their oligosaccharide content using beta-elimination conditions. Changes in glycosylation are monitored by matrix-assisted laser desorption/ionization Fourier transform ion cyclotron resonance mass spectrometry… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

12
255
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 206 publications
(267 citation statements)
references
References 27 publications
(45 reference statements)
12
255
0
Order By: Relevance
“…Indeed, the profiling of serum glycans has been performed previously as a screen for distinct potential glycan biomarkers of ovarian cancer and breast cancer. 18,19 Hence, we surmised that highly specific glycoprotein markers of HCC should be detected by monitoring the serum glycosylation profile in these patients. In glycan structure, both G2890 and G3560 are multiply branched (G2890 is tri-antennary and G3560 is tetra-antennary) glycans with a core fucose.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, the profiling of serum glycans has been performed previously as a screen for distinct potential glycan biomarkers of ovarian cancer and breast cancer. 18,19 Hence, we surmised that highly specific glycoprotein markers of HCC should be detected by monitoring the serum glycosylation profile in these patients. In glycan structure, both G2890 and G3560 are multiply branched (G2890 is tri-antennary and G3560 is tetra-antennary) glycans with a core fucose.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, some glycoproteins have been suggested as biomarkers of human carcinomas such as ovarian cancer, breast cancer, and HCC. [16][17][18][19] Of note, changes to the N-linked glycan modification of glycoproteins occur during the tumorigenesis and progression of HCC lesions. However, the correlation between the N-glycan profile and tumorassociated characteristics such as the degree of malignancy and prognosis has not been previously evaluated in HCC.…”
mentioning
confidence: 99%
“…Proposed mechanism for high levels of sialic acid could be the change in sialylation that occurs before cancer development. Recently, An et al [31] developed the glycomic approach to identify oligosaccharide markers for ovarian cancer. Globally released oligosaccharides from O-linked glycoproteins can be harvested and could serve as biomarkers for ovarian cancer.…”
Section: Discussionmentioning
confidence: 99%
“…In a study on human pancreatic cancer, serum samples contained N-glycans with increased fucosylation and sialylation relative to those from healthy individuals [24]. Samples in the study of ovarian cancer patients also showed a number of neutral oligosaccharides that appeared related to cancer [25]. Despite intense research efforts, many times the findings are relevant only to the particular biological material on which the analysis was performed.…”
mentioning
confidence: 99%